2003
DOI: 10.1029/2002ja009373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solar wind pressure pulses on the size and strength of the auroral oval

Abstract: [1] It has recently been found that solar wind dynamic pressure changes can dramatically affect the precipitation of magnetospheric particles on the high-latitude ionosphere. We have examined the effect of large solar wind dynamic pressure increases on the location, size, and intensity of the auroral oval using particle precipitation data from Defense Meteorological Satellite Program (DMSP) spacecraft. Three events have been selected for study during the time period after 1997 when four DMSP spacecraft (F11-F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
199
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(229 citation statements)
references
References 38 publications
27
199
0
1
Order By: Relevance
“…Figure 3 shows another model-data comparison by projecting the satellite observations and the corresponding model parameters on a polar view of the northern hemisphere. The left column of Figure 3 displays near simultaneous orbit tracks by DMSP F15 (panels a, b, and c), and CHAMP and GRACE (panel d), shortly after the shock impact of~6:10 UT and after the magnetosphere was strongly compressed, which is typically followed by strong enhancements of auroral precipitation and ionospheric electric fields (Zesta et al 2000;Boudouridis et al 2003Boudouridis et al , 2008Boudouridis et al , 2011. Figures 3a-3c The DMSP F15 spacecraft observes~120 mV/m of enhanced total electric field near 14 MLT and 70°MLAT as seen in Figure 3a.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows another model-data comparison by projecting the satellite observations and the corresponding model parameters on a polar view of the northern hemisphere. The left column of Figure 3 displays near simultaneous orbit tracks by DMSP F15 (panels a, b, and c), and CHAMP and GRACE (panel d), shortly after the shock impact of~6:10 UT and after the magnetosphere was strongly compressed, which is typically followed by strong enhancements of auroral precipitation and ionospheric electric fields (Zesta et al 2000;Boudouridis et al 2003Boudouridis et al , 2008Boudouridis et al , 2011. Figures 3a-3c The DMSP F15 spacecraft observes~120 mV/m of enhanced total electric field near 14 MLT and 70°MLAT as seen in Figure 3a.…”
Section: Resultsmentioning
confidence: 99%
“…Because their auroral keogram shows a similar fading even before the SC, we think that the fading is due to other dynamic processes of DP-2 currents unrelated to the SC and that PI currents occur equatorward of preexisting DP-2 (discrete aurora) well within closed magnetic field lines. Boudouridis et al (2003) showed that the polar cap shrinks after shocks. Although we did not see such poleward expansions within our imager FOV, this could be because we focused on several minutes around the SC onset times, whereas they were concerned with changes over longer time scales.…”
Section: Resultsmentioning
confidence: 99%
“…Imaging from space and ground has demonstrated the capability of detecting auroral intensifications associated with solar wind dynamic pressure enhancements (e.g., Zhou and Tsurutani 1999;Boudouridis et al 2003;Meurant et al 2004;Liou et al 2007;Holmes et al 2014). A proton and electron diffuse aurora intensifies in the post-noon and pre-noon sectors and propagates antisunward.…”
Section: Introductionmentioning
confidence: 99%
“…Large tail lobe SI events can occur during both southward and northward IMF, but under southward IMF conditions, they are particularly likely to influence tail dynamics. For example, to explain the widening of the auroral oval and the decrease in the polar cap size during solar wind pressure pulses, Boudouridis et al (2003) suggested that the compression of the magnetotail can significantly increase nightside reconnection. The response of the near-Earth plasma sheet during tail lobe SIs will be the subject of future work.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Low-latitude magnetograms record rapid perturbations called sudden impulses (SI), or storm sudden commencements (SSC) if a geomagnetic storm follows, see (Araki, 1977;Smith et al, 1986;Araki, 1994;Lee and Hudson, 2001). Especially for the southward interplanetary magnetic field (IMF), pressure pulses cause almost immediate and global enhancements in ionospheric currents and auroral precipitation, see (Zhou and Tsurutani, 1999;Zesta et al, 2000;Boudouridis et al, 2003;Meurant et al, 2003). In the tail lobes, sudden increases in the magnetic field have been observed on time scales from a few to ten minutes, see (Sugiura et al, 1968;Kawano et al, 1992;Collier et al, 1998;Kim et al, 2004).…”
Section: Introductionmentioning
confidence: 99%